Integration on ergonomic risk factors to improve worker’s comfort level in composite trimming process - Shukur, Azurin (2022)
In today’s manufacturing industry especially the aircraft composite panel manufacturing sector, matters related to ergonomic risk factors are given less attention. This causes 20% of workers to take sick leave in a week due to the method of the process itself and this affects the production with a decrease of 16% to 20% per week. In addition, there are no previous studies that combine vibration, work environment factors and body posture to show a comprehensive effect on workers’ health and comfort. This study was conducted to identify matters related to ergonomic factors on the worker’s comfort level. It also to formulate and integrate ergonomic risk factors during the cutting process. The next objective is to verify the level of employee comfort by using the RULA and REBA methods. To achieve the first objective, a survey method using a survey form was used to obtain feedback on the level of workers’ comfort for 12 situations of comfort that existed when the composite cutting process was performed and then subsequently performed a descriptive analysis. To achieve the second objective, vibrations from hand tools were obtained using a vibrometer and analyzed using Minitab software to produce a regression equation at a panel thickness of 3 mm. Working environment factors such as air humidity, temperature, noise and lighting at the composite cutting area for both open and close area were measured using specific measuring tools and then analyzed using Minitab software and from this analysis automatically generate regression equations for working environment factors for indoor and open workplaces. For body posture, the moment when the worker was cutting the panel was studied using the RULA and REBA methods. The results of the survey method from the descriptive analysis showed that the workers were uncomfortable for the twelve work situations presented. Studies for the working environment show that the open workplace is in a comfortable situation while the indoor place is less comfortable. For body posture, show scales value of 6 and 7 by using RULA and scale 8 to 11 by using REBA. This scale means that the process or posture needs to be studied immediately or changed as soon as possible and by using the same method, the industry players will be able to perform the necessary improvement actions or interventions until they reach the allowable RULA and REBA value. This study has been able to provide a useful output in which the generated regression equations will be used by manufacturing industry players related to composite cutting process to know and control the vibration level from hand tools. By using regression equations for working environment factors, the industry players will be able and easily to control the working environment at their composite cutting site to ensure the comfort level of their workers is maintained.